Combined practice and learning of structure and parameters of the volleyball serve in beginners - Cintia Matos; Rodolfo Benda; Marcelo Januário; Cícero Luciano Costa; Arthur Ferreira; Matheus Lucas; Flávio Marinho; Guilherme Lage; Herbert Ugrinowitsch (Asociación Española de Ciencias del Deporte, 2021)
This study aimed to investigate the combined practice schedule on the learning of both movement pattern and parameters of a complex sports motor skill. Sixteen participants (14.19 ± 1.80 years-old) were counterbalanced into two groups, random practice and combined practice, based on pretest performance. During the acquisition phase, the participants performed 252 trials of the Japanese volleyball serve divided equally into six sessions. The movement pattern and parameters measures were analyzed on pretest and retention test. The results showed that combined practice led to movement pattern improvement and random practice improved parameters. These results give support to the proposition that movement pattern and parameters have distinct structures of control. Also, the results indicate that combined practice needs a higher amount of random practice to promote parameters improvement.